Engineering the Eternal City infrastructure, topography, and the culture of knowledge in late sixteenth-century Rome - Long, Pamela O. (University of Chicago Press, 2018)
Intro -- Contents -- Money, Weights, and Measures -- Author's Note -- Introduction: Rome: Portrait of the Late Sixteenth-Century City -- 1. Troubled Waters: The Tiber River -- 2. The Streets and Sewers of Rome -- 3. Repairing the Acqua Vergine: Conflict and Process -- 4. Contested Infrastructure -- 5. Roman Topography and Images of the City -- 6. Maps, Guidebooks, and the World of Print -- 7. Reforming the Streets -- 8. Engineering Spectacle and Urban Reality -- Conclusion: A City in Transition -- Acknowledgments -- List of Abbreviations -- Notes -- Bibliography -- Index